2005
DOI: 10.1111/j.1523-1755.2005.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effect of nocturnal hemodialysis on blood pressure, left ventricular hypertrophy, anemia, mineral metabolism, and health-related quality of life

Abstract: Nocturnal hemodialysis is a potential alternative to conventional intermittent hemodialysis. Before significant resources are invested in initiating nocturnal hemodialysis programs, further data on mortality and cardiovascular morbidity, preferably from randomized clinical trials, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
155
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 59 publications
2
155
2
2
Order By: Relevance
“…Monitoring of a hematocrit-guided ultrafiltration algorithm lowered hospitalization for fluid overload and hypertension among pediatric HD patients (27). Cardiovascular admissions are higher on the day following the longest interdialytic interval in HD patients (28,29); therefore, alternative dialysis schedules deserve further study to determine their impact on hospitalization and readmission (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of a hematocrit-guided ultrafiltration algorithm lowered hospitalization for fluid overload and hypertension among pediatric HD patients (27). Cardiovascular admissions are higher on the day following the longest interdialytic interval in HD patients (28,29); therefore, alternative dialysis schedules deserve further study to determine their impact on hospitalization and readmission (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] More frequent hemodialysis has been suggested to approximate continuous glomerular filtration; improvements in BP and phosphorus clearance have frequently been observed. [4][5][6] Whether such mechanisms result in lower mortality risk is unknown, as observational studies that have reported improved survival with more frequent dialysis were relatively small and/or incompletely adjusted for selection bias. [7][8][9][10][11] The popularity of home hemodialysis has recently risen in the United States.…”
mentioning
confidence: 99%
“…These physiologic restorative properties of NHD have been discussed in detail elsewhere and were the subject of a recent systematic review (6)(7)(8)(9). The majority of NHD research has been conducted by a small group of clinical research teams worldwide with a limited number of NHD patients.…”
Section: Methodologic Limitations Of Existing Researchmentioning
confidence: 99%